Perhitungan Jumlah Bahan Kimia pada External Water Treatment (Studi Kasus di PMKS XYZ, Kalimantan Tengah) - Istianto Budhi Rahardja (JURNAL CITRA WIDYA EDUKASI, 2019)
The Water Treatment Plant is a process of purifying water in a palm oil mill (POM), consisting of external water treatment and internal water treatment which purpose to treat raw water into water that is suitable for use as needed. Addition of chemical with doses that are in accordance with the result of the Jar test will give result that are in accordance with the quality standard parameters in the external water treatment. The determination of these chemicals at PT XYZ has not been in accordance with the composition of raw water processed on that day, thus causing the quality of the water produced to not be in accordance with the specified quality standards and the use of these chemicals to be ineffective and inefficient. The purpose of this research was to determine how to determine the dosage and amount of chemical needed for more effective and efficient water treatment in external water treatment. The result of the research show that the result of the jar test carried out every day will produce a dose of chemical and the number of their needs will be more effective and efficient.